Analysis and optimization design of control signal line parasitic effects on streaking phenomenon in CMOS image sensor. (March 2023) - Zhang, Yuanmeng; Xu, Jiangtao; Nie, Kaiming; Liu, Changju; Yang, Yuli; Wang, Hao
Abstract: This paper presents an optimization scheme for charge transfer control signal (TX) line to suppress the streaking phenomenon in CMOS image sensor (CIS) with FD-Shared. The influence of the streaking phenomenon in the image is evaluated by the increment of dark pixels. By building the mathematical model of streaking phenomenon, the relationship between the size of TX line and the increment of dark pixels is revealed. The simulation results show that for a 6.144 cm (H) × 8.192 cm (V) pixel array under 110 nm CMOS process, when the width of the TX line is 0.4 μm, the increment of dark pixels is the smallest. The minimum increment is 0.1709 DN at 0 dB and 2.7080DN at 24 dB. The increment is linearly amplified by the readout circuit gain. In the chip design, the streaking phenomenon can be alleviated according to the model analysis and optimization scheme given in the paper.